HYGIENE MEASURES IN IMPROVING THE ENVIRONMENT (CASE STUDY: THE WARD BATANG ARAU PADANG SELATAN DISTRICT OF PADANG CITY) - Wibowo, Agung Tri; Elfemi, Nilda; Yasin, Faishal (Pendidikan Sosiologi, 2014)
This research was motivated by the problems and circumstances Trunk Arau Village Community Environment Southern District of Padang City. In this case to see how environmental conditions and circumstances masyarakatnya. Purose this study is to describe 1 ). Community Efforts to Improve Environmental Hygiene in the village of Batang Arau. 2 ). Constraints in Improving Public Health in Urban Environment Batang Arau. Methods The study used a qualitative approach with descriptive type. Intake of informants used by purposive sampling. The type of data in this study there are two primary data and secondary data. The data collection technique is the technique of interview, observation and documentation, using a tool such as interview guides, books, pens and cell phone. After the data were analyzed by means of the data is reduced, data display and data verification ( conclusion ). The results of the study revealed tha, 1 ) Community efforts to improve environmental hygiene in the village of Batang Arau, namely: ( a ) Mutual Aid, ( b ) Procurement trash every home residents, ( c ) Throw garbage into the garbage containers provided by the Government, ( d ) Burning trash, ( e ) Rework garbage, ( f ) Reduce usage of materials that could be rubbish. 2 ) Obstacle in the improvement of environmental hygiene in the village of Batang Arau, namely: ( a ) Lack of public awareness, ( b ) Lack of socialization, ( c ) Trash submissions from the next village, ( d ) The location of the tank is not quite right, ( eÂ ) The lack of trash from city office, ( fÂ ) The state of the damaged bins.Â